Comparison of EMG signal of the flexor hallucis longus recorded using surface and intramuscular electrodes during walking. (October 2021) - Knox, Jessica; Gupta, Amitabh; Banwell, Helen A.; Matricciani, Lisa; Turner, Deborah
Abstract: The purpose of this study was to compare the use of intramuscular (iEMG) and surface (sEMG) electromyography electrodes to record flexor hallucis longus (FHL) muscle activity during walking, and describe the role of the FHL. Muscle activity was recorded in 12 participants using sEMG and iEMG during treadmill and overground walking. Inter-tester reliability for visual detection of onset and offset of muscle activity was high (ICC = 1.00). During the loading period, the number of bursts of muscle activity was statistically significantly greater using iEMG compared to sEMG when treadmill walking (p = 0.016), and the duration of muscle activity was significantly greater for iEMG (p = 0.01) on both walking surfaces. There were no differences for peak and mean root mean squared (p ≥ 0.07). The FHL activity observed during the loading period (heel strike to forefoot strike) supports the function of the FHL to act as a dynamic ankle stabiliser of the rearfoot, as well as contributing to propulsion during the latter part of stance. The choice of electrodes to detect FHL activity should be dependent on whether the loading and propulsive periods are of interest, and whether treadmill or overground walking will be examined.